What is a Cochrane review? - Cipriani, A; Furukawa, T; Barbui, C (2011)
Systematic reviews carried out by Cochrane Collaboration (an international network of researchers belonging to this independent, not-for-profit organization) are recognized worldwide as the highest standard in evidence-based healthcare. The main reason is that Cochrane reviews follow a common and specific methodology to limit bias and random error. In this issue, we highlight the most important methodological features of Cochrane reviews, also reporting details on the editorial process to publish the review in the Cochrane Library.